Organic matter and shading on ion accumulation in soil cultivated with noni under salinity - Maria C. M. R. de Souza; Letícia K. B. de Oliveira; Rafael S. da Costa; Ademir S. Menezes; Aiala V. Amorim; Claudivan F. de Lacerda (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the influence of organic matter on the salt accumulation in three layers of soil cultivated with noni plants irrigated with brackish water, in open field and under partial shading conditions. The experimental design was in randomized blocks, arranged in a split-split-plot scheme with five replicates. The plots were constituted by the cultivation environments (open and shaded field), the subplots by the electrical conductivity of the irrigation water (0.3, 1.5, 3.0, 4.5, and 6.0 dS m-1), and the sub-subplots by the absence and presence of organic matter. At 110 days after application of the treatments, the electrical conductivity of the saturation extract and the potassium, sodium, calcium, and magnesium concentrations were determined in three soil layers (0-10, 10-20, and 20-30 cm). Partial shading reduced the total accumulation of salts and sodium in the soil compared to the open field. Increasing the electrical conductivity of irrigation water reduced potassium concentrations in the soil, but this effect is offset by the addition of organic matter, which releases potassium, calcium, and magnesium for plant nutrition. However, cattle manure increases sodium accumulation in the soil in treatments with the highest water salinity.